Diversity of MDE Toolboxes and Their Uncommon Properties - Teixeira, Paulo Gabriel; Lebtag, Bruno Gabriel Araújo; Basso, Fábio Paulo (Anais do Workshop em Modelagem e Simulação de Sistemas Intensivos em Software (MSSiS); 2020: Anais do II Workshop em Modelagem e Simulação de Sistemas Intensivos em SoftwareDO - 10.5753/mssis.2020.12489, 2020)
Model-Driven Engineering (MDE) has reached some maturity. Due to that, a high diversity of technologies and platforms have emerged to support the resolution of a range of problems and contexts in which MDEis adopted as a solution. As a consequence, when some level of reuse of those artifacts (such as model transformations, Domain-Specific Languages(DSLs) and refinement tools), difficulties are faced due to the high diversity of formats in which all those assets are specified. Since we noted this trend, we decided to search for instances in the literature that supports our hypothesis of a high degree of diversity in MDE artifacts in the state of the practice. Thus, we carried out an exploratory literature review. As a result, we summarized key studies used as input to build a search string adopted to structure a future systematic literature review. Our study contributes by classifying nine types of MDE toolboxes with uncommon properties than those usually found in MDE workbenches.